The Effectiveness of Guidance and Counseling Teacher Development Patterns on Student Learning Achievement: A Comparative Study Between Islamic and Non-Islamic Islamic Boarding Schools - Nurfadillah Kasim; Sandi Pratama; Ratna Wulandari (Universitas PGRI Yogyakarta, 2026)
This study examines the effectiveness of Guidance and Counseling Teacher development patterns on student learning achievement through a comparative analysis of Islamic and non-Islamic boarding schools. A quantitative method using a questionnaire-based survey was employed to collect data from 20 students (10 from each school type) across 13 indicators measuring coaching planning, service implementation, supervision, and evaluation. The results reveal significant contextual differences: Islamic boarding school students demonstrated higher discipline and motivation due to 24-hour supervision and internalization of religious values yet showed greater variation in perceived coaching effectiveness (total scores ranging from 17 to 70). Conversely, non-Islamic boarding school students exhibited more homogeneous perceptions (scores 33–41), indicating a more structured but less deeply integrated coaching approach. Regression analysis showed a low correlation (Multiple R = 0.396) and a non-significant influence (p > 0.05) of the coaching pattern on achievement, suggesting that external factors explain 84.31% of the variance in learning outcomes. The study concludes that GC coaching effectiveness is highly context-dependent: Islamic boarding schools’ environments foster deeper character integration, whereas non-Islamic boarding schools offer more systematic yet reactive interventions. Recommendations include developing culturally responsive, value-based counseling training for GC teachers and establishing continuous, data-driven evaluation mechanisms to enhance academic and non-academic student outcomes. Keywords: guidance and counseling, coaching patterns, learning achievement, Islamic boarding school, student development